PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERORIENTASI KETERAMPILAN PROSES SAINS PADA MATERI UNSUR UNTUK SISWA TUNARUNGU KELAS XI DI SMALB-B (DEVELOPMENT OF STUDENT ACTIVITY SHEET (LKS) PROCESS ORIENTED SCIENCE SKILLS ON INGREDIENTS MATERIAL FOR DEAF STUDENT IN CLASS XI SMALB-B) (UNESA Journal of Chemical Education, 2017)
This aim of research is develop science process skills studentts activity sheet advisability for training science process skills student with hearing impairment. The method of this study used a Research and Development (R & D) with 6 deaf students’s subject of SMALB Karya Mulya Surabaya. The research’s instrument that used are review sheet, validation sheet, observation of science process skills activities sheet, examination sheet, and questionnaire sheet of student responses. Technique of data collection consist of study, validation, observation, and test then analysed by descriptive. LKS is considered feasible, if get percentage of ≥61% with good or very good criterion. The results showed that the student worksheet oriented science process skills on material developed element has been theoretical and empirical feasibility for use as a learning media. The theoretic advisability is validation results consist of content, language, presentation, and graphic criteria with percentage range are 66,67% - 100%; 66,67% - 75%; dan 66,67% - 75%. So it can said that the students activity sheet paper with good and very good criteria. While the empirical feasibility that are observation of science process skills activity gets a percentage interval between 83.33% - 100% feasible with very good, a final test all got a score of 83.33, and a student questionnaire responses received percentage interval between 66.67% - 100% feasible with good and ver good criteria. Keyword : Student worksheet, Science process skill, Deaf